2007
DOI: 10.1038/sj.onc.1210707
|View full text |Cite
|
Sign up to set email alerts
|

HDM2 antagonist Nutlin-3 disrupts p73-HDM2 binding and enhances p73 function

Abstract: Nutlin-3, a small molecule inhibitor, activates p53 by disrupting p53-HDM2 association. In this study, we found that Nutlin-3 suppressed cell growth and induced apoptosis in the absence of wild-type p53, suggesting a p53-independent mechanism for Nutlin-3-induced cell death. Like p53, its homolog p73 transactivates proapoptotic genes and induces cell death. Since HDM2, a key negative regulator of p53, also binds to and inhibits p73, we asked whether p73 could mediate Nutlin-3-induced apoptosis. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(181 citation statements)
references
References 29 publications
10
169
1
1
Order By: Relevance
“…Indeed, we observed highly elevated levels of p73 in the highly sensitive cell lines with mutated Rb, whereas depletion of E2F-1 by siRNA transfection decreases the protein levels of p73 ( Figure 5B). Furthermore, as it has been shown that Nutlin-3 stabilizes p73 and induces p73-mediated apoptosis in p53À/À cells by disrupting p73-binding of Mdm2 (Lau et al, 2008), we also observed that Nutlin-3 inhibits the ability of Mdm2 to bind p73 and stabilizes p73 in wild-type p53 cells with mutated Rb (Supplementary Figure 4), resulting in a significant apoptotic response to Nutlin-3 ( Figure 3D). In contrast, depletion of p73 by siRNA transfection markedly suppresses Nutlin-3-induced apoptosis in these cell lines ( Figure 5C), suggesting that p73 is important for E2F-1-mediated apoptosis induced by Nutlin-3 in p53 wild-type cancer cells, particularly, with mutated Rb.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, we observed highly elevated levels of p73 in the highly sensitive cell lines with mutated Rb, whereas depletion of E2F-1 by siRNA transfection decreases the protein levels of p73 ( Figure 5B). Furthermore, as it has been shown that Nutlin-3 stabilizes p73 and induces p73-mediated apoptosis in p53À/À cells by disrupting p73-binding of Mdm2 (Lau et al, 2008), we also observed that Nutlin-3 inhibits the ability of Mdm2 to bind p73 and stabilizes p73 in wild-type p53 cells with mutated Rb (Supplementary Figure 4), resulting in a significant apoptotic response to Nutlin-3 ( Figure 3D). In contrast, depletion of p73 by siRNA transfection markedly suppresses Nutlin-3-induced apoptosis in these cell lines ( Figure 5C), suggesting that p73 is important for E2F-1-mediated apoptosis induced by Nutlin-3 in p53 wild-type cancer cells, particularly, with mutated Rb.…”
Section: Discussionmentioning
confidence: 57%
“…47,48 Recent studies have shown that nutlin-3a, at very high concentrations, usually 420-30 mM, can inhibit the growth of cancer cells with deleted p53, or harbouring a nonfunctional, mt p53 gene, although the exact mechanism is incompletely understood. 35,36 It seems, depending on the in vitro system, that activation of other partners of Mdm2, including p73 or E2F1, may be involved in this phenomenon. 35,36 Accordingly, we showed here that nutlin-3a can enhance the cytotoxicity of doxorubicin chemotherapy against ALK þ ALCL cells harbouring nonfunctional mt p53, associated with increased p73 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various studies have shown that very high doses of nutlin-3a, at the range of 20 mM to 430 mM, can induce cytotoxicity and inhibit the growth of cancer cells harbouring a nonfunctional mt p53 gene, through effects on partner proteins of Mdm2 other than p53, including the p53-related protein p73 and E2F1. [34][35][36] As these targets also can be affected by genotoxic chemotherapeutic agents, we investigated the potential effect of nutlin-3a on the anti-tumour activity of doxorubicin against ALK þ ALCL cells harbouring nonfunctional, mt p53.…”
Section: P53 Reactivation In Alcl E Drakos Et Almentioning
confidence: 99%
“…37 As p53 is rarely mutated in hematologic malignancies, many studies have been carried out on various types of tumor cell, including chronic lymphocytic leukemia B cells (B-CLL), 18,20 myeloma, 14 Kaposi sarcoma herpes virus (KHSV)-induced lymphoma 13,38 and Hodgkin's lymphoma. 19 In some cases, nutlin-3 is also able to induce apoptosis in p53-inactivated cells through a p73-dependent mechanism 39 and, as shown recently in a mantle cell lymphoma cell line carrying mutated p53, to synergize with drugs. 40 All these studies have suggested that nutlin-3 may indeed be considered, alone or in combination with various genotoxic drugs, as a novel therapeutic approach for patients.…”
Section: Discussionmentioning
confidence: 99%